2021
DOI: 10.3390/biology10111210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12 Weeks Core Training on Core Muscle Performance in Rhythmic Gymnastics

Abstract: Background: Rhythmic gymnastics performance is characterized by technical elements involving flexibility, aerobic capacity and strength. Increased core strength in rhythmic gymnastics could lead to improved sporting performance. Objective: The aim of this study was to analyze the effect of 12 weeks of core muscle training on core muscle performance in rhythmic gymnasts. Methods: A randomized controlled study involving 24 rhythmic gymnastics was conducted. Participants were randomly assigned to a control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
0
18
0
2
Order By: Relevance
“…The authors concluded that CST is an effective plan for improving the physical and technical characteristics of young female Malaysian rhythmic gymnasts. Similarly, another recent study reported core strength improvements in young rhythmic gymnasts after a twelve-week traditional CST [ 26 ]. Nonetheless, these authors did not carry out an integrated functional CST for RG.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The authors concluded that CST is an effective plan for improving the physical and technical characteristics of young female Malaysian rhythmic gymnasts. Similarly, another recent study reported core strength improvements in young rhythmic gymnasts after a twelve-week traditional CST [ 26 ]. Nonetheless, these authors did not carry out an integrated functional CST for RG.…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, there are only two studies measuring CS after a CST program among rhythmic gymnasts [ 25 , 26 ]. Most available research is focused on conducting CST for rehabilitation, preventing, and reducing the risk of injury in sports [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have investigated the effects of core muscle training programs on a variety of characteristics of physical fitness. Most studies were related to muscle strength and power, such as leg muscle strength, abdominal muscle strength, and balance in male students of physical education and recreation health ( Firdauz and Setijono, 2018 ), core muscle strength and endurance in school’s football team players ( Boyaci and Tutar, 2018 ), isometric leg and back muscle strength, abdominal muscle strength, back extensor endurance, dynamic balance, flexibility of the lower back and hamstring muscles, thoracic and lumbar spine ROM and lateral bending in male university students ( Yaprak, 2018 ), balance, agility and explosive force in runners ( Dinç and Ergin, 2019 ), neuromuscular control of the trunk and lower limbs during jump landing and single-legged squatting in female collegiate basketball players ( Sasaki et al, 2019 ), core muscle strength in young male cyclists ( Chok, 2020 ), core muscle strength in professional football players ( Etxaleku et al, 2020 ), core muscle strength in junior swimmers ( Marani et al, 2020 ), endurance, strength and balance in female students with trunk defects ( Mohebi Rad and Norasteh, 2020 ), core muscle performance in rhythmic gymnasts ( Esteban-García et al, 2021 ), and neuromuscular control and strength of the trunk muscles in pediatric soccer players ( Kumahara et al, 2021 ). Other studies were related to balance, endurance and flexibility, for instance endurance, strength, flexibility and balance in sedentary women ( Sekendiz et al, 2010 ), dynamic balance, spinal mobility, functional mobility and trunk muscle strength in older adults ( Granacher.…”
Section: Resultsmentioning
confidence: 99%